Integrating product lifecycle management systems with maintenance information across the supply chain for root cause analysis - Madenas, Nikolaos (Cranfield University, 2014)
Purpose: The purpose of this research is to develop a system architecture for integrating PLM systems with maintenance information to support root cause analysis by allowing engineers to visualise cross supply chain data in a single environment. By integrating product-data from PLM systems with warranty claims, vehicle diagnostics and technical publications, engineers were able to improve the root cause analysis and close the information gaps. Methodology: The methodology was divided in four phases and combined multiple data collection approaches and methods depending on each objective. Data collection was achieved through a combination of semi-structured interviews with experts from the automotive sector, by studying the internal documentation and by testing the systems used. The system architecture was modelled using UML diagrams. Findings: The literature review in the area of information flow in the supply chain and the area of root cause analysis provides an overview of the current state of research and reveals research gaps. In addition, the industry survey conducted, highlighted supply chain issues related to information flow and the use of Product Lifecycle Management (PLM) systems. Prior to developing the system architecture, current state process maps were captured to identify challenges and areas of improvement. The main finding of this research is a novel system architecture for integrating PLM systems with maintenance information across the supply chain to support root cause analysis. This research shows the potential of PLM systems within the maintenance procedures by demonstrating through the integration of PLM systems with warranty information, vehicle diagnostics and technical publications, that both PD engineers and warranty engineers were benefited. The automotive experts who validated the system architecture recognised that the proposed solution provides a standardised approach for root cause analysis across departments and suppliers. To evaluate the applicability of the architecture in a different industry sector, the proposed solution was also tested using a case study from the defence sector. Originality/Value: This research addressed the research gaps by demonstrating that: i) A system architecture can be developed to integrate PLM systems with maintenance information to allow the utilisation of knowledge and data across the product lifecycle; ii) Network can be treated as a virtual warehouse where maintenance data are integrated and shared within the supply chain; iii) Product data can be utilised in conjunction with maintenance information to support warranty and product development engineers; iv) Disparate pieces of data can be integrated where later data mining techniques could potentially be applied.